A flood of information: Using Sentinel-3 water colour products to assure continuity in the monitoring of water quality trends in the Great Barrier Reef (Australia). (15th October 2019) - Petus, Caroline; Waterhouse, Jane; Lewis, Stephen; Vacher, Michael; Tracey, Dieter; Devlin, Michelle
Abstract: An operational method to assess trends in marine water composition and ecosystem health during flood periods has been developed for the Great Barrier Reef (GBR), Queensland, Australia. This method integrates satellite water colour data with field water quality and ecosystem monitoring data and involves the classification of Moderate-Resolution Imaging Spectroradiometer (MODIS satellite) pixels into six distinct water bodies using a "wet season" colour scale developed specifically for the GBR. Using this information, several monitoring and reporting products have been derived and are operationally implemented into a long-term water quality monitoring program for the GBR. However, MODIS sensors are aging and a long-term monitoring solution is needed. This study reviewed the water colour monitoring products currently used in the GBR. It tested the feasibility to transition these methods from historical MODIS satellite imagery to the new Sentinel-3 satellite of the European Space Agency and from the wet season colour scale to the historical Forel-Ule colour scale, using a freely-distributed Forel Ule (FU) Satellite Toolbox. Monitoring products derived from both satellites and colour scales showed very similar patterns across two case study regions of the GBR, the Wet Tropics and Burdekin marine regions, over the 2017-18 wet season. The results obtained in this study highlighted the potential of using FU Sentinel-3 imagery for the mapping of GBR marine water bodies, including flood conditions. Furthermore, the operational monitoring products and frameworks developed for the GBR are likely to provide valuable foundations for analysis of FU Sentinel-3 data in the future. Such satellite water colour datasets and frameworks will be instrumental to better understand the impact of floods and reduced water clarity on marine ecosystems, as well as to support water quality management and facilitate catchment management policy in the GBR and worldwide. Highlights: Remote sensing data help assessing water quality trends in the Great Barrier Reef. Current monitoring products using MODIS-retrieved water colour data are reviewed. New Sentinel-3 satellite data and the historical Forel-Ule colour scale are tested. These new data and methods are efficient to map marine water bodies in the GBR. They help understanding the impact of floods and support water quality management.